2022
DOI: 10.1093/eurpub/ckac100
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a community intervention to reduce social isolation among older people in low-income neighbourhoods

Abstract: Background Social and demographic trends show a global increase of proportion of older people at risk of social isolation. This study aimed to evaluate the effectiveness of an intervention conducted in low-income neighbourhoods to reduce social isolation and its negative effects on health in older persons. Methods A quasi-experimental study with a comparison group was performed. The ‘School of Health for Older People’ is a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[24], [25]. However, the evidence gathered is still limited, and further research is needed to fully understand the potential impact of these interventions and how to maximise their effectiveness [26], [27]. Interventions evaluated in such studies include unconditional cash transfers, income tax credits, minimum wage policies, and community-based participatory interventions [26].…”
Section: Role Of Legal Educationmentioning
confidence: 99%
“…[24], [25]. However, the evidence gathered is still limited, and further research is needed to fully understand the potential impact of these interventions and how to maximise their effectiveness [26], [27]. Interventions evaluated in such studies include unconditional cash transfers, income tax credits, minimum wage policies, and community-based participatory interventions [26].…”
Section: Role Of Legal Educationmentioning
confidence: 99%
“… 6 Actually, different authors have shown the beneficial effects of community intervention, which improve mental health, quality of life (QOL) and social support in older people. 7 Beyond the clinical setting, pleasure, creativity and social support promoted by music-related activities positively influence self-confidence and self-esteem, showing transversal effects among and within individuals. 8 Exploring closely related themes, other scholars have found that music training improves social and subjective (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, many previous studies have focused on the direct effects of social support on the physical and mental health of older adults, little is known about their underlying mechanisms. Furthermore, the correlation between social support and personal health has been analyzed in existing studies (12), and Internet use may have effects on social support (13)(14)(15). Therefore, whether and how social support mediates the relationship between Internet use and older adults' health status remains to be further tested.…”
mentioning
confidence: 99%